APLIKASI RIZOBAKTERI PADA COVER CROP DALAM MEMPENGARUHI SIFAT KIMIA TANAH BEKAS TAMBANG NIKEL - Leomo, Sitti; Mudi, La; Alam, Syamsu (Jurnal Agroteknos, 2013)
The research aimed to know the efectifity of cover crop applied with rhizobacteria to influence chemical characteristic of  soil of  ex-nickel mine. This research was conducted since May to August 2012 at experimental farm and Agrotechnology Laboratory of Faculty of Agriculture of  Haluoleo  University. Soil  analysis  was  carried  out  been  in  Soil  Research Institute Bogor. The experiment was designed in a randomized block design, in a factorial pattern. The first factor was application of rhizobacteria consisted of 2 levels : R0 (without application of rhizobacteria) and R1 (with application of rhizobacteria). The second factor was cover crop with 4 levels, namely : C1  (Centrosema pubescens Benth.), C2  (Calopogonium mucunoides), C3  (Crotalaria sp.) and C4  (Amaranthus spinosus L.), resulted in 8 treatment combination. Each treatment was repeated 3 times, resulted in 24 experimental units. The experimental data were  analyzed using analysis of variance and then followed by Least Significant Differences Test. Soil analysis data were analyzed descriptively. The research results showed that the application of rhizobacteria at Crotalaria sp. (C3) gave a significant effect on crop height and number of leaf branch. Besides, application of cover crop and rhizobacteria at ex-nickel mine increased soil chemical characteristic C organic, N total, P2O5, HCl 25% and K-ddKey words :   Rhizobacteria, cover crop, soil chemical, nickel mining